Health information in a changing world practical approaches for teachers, schools, and school librarians - Lukenbill, W. Bernard; Immroth, Barbara Froling (Santa Barbara, Calif. Libraries Unlimited, 2010)
Schools, libraries, and health education -- Health curriculum and instruction -- Teaching and holistic health information literacy -- Searching for health information and developing library use skills -- Materials for health instruction and information -- Literature, the arts, performance activities, and languages -- Connections to good health : social and behavioral sciences, and languages -- Connections : health, physical education, science, and mathematics -- Globalization, instruction, and youth health -- Outreach, health, and the school community -- Into the future : health, curriculum, and librarians
Includes bibliographical references (p. [209]-229) and index
Keywords: Health education (Elementary); Health education (Secondary); Health education -- Curricula; Health education -- Curricula -- United States; School librarian participation in curriculum planning; Children -- Health and hygiene -- Information services; Youth -- Health and hygiene -- Information services